Pemanfaatan Geographic Information System Geografis (Sig) Sebagai Alat Komunikasi Digital dalam Pemetaan Sebaran Pariwisata di Kabupaten Kebumen - Subekti , Fajar; ., Purwadi; Irdarian, Rizki Reziana (Jurnal Sains dan Teknologi (JSIT), 2025)
The primary challenge addressed by this research is the insufficient digital communication and visualization of tourism assets in Kebumen Regency, which hinders effective public information dissemination, planning, and promotion. Existing methods often rely on static, non-interactive maps or textual data, failing to provide an accessible and dynamic spatial understanding of diverse tourist sites, their distribution, and accessibility. This lack of digital clarity leads to suboptimal visitor experiences and inefficient allocation of tourism development resources.The main objective of this study is to analyze the effectiveness of Geographic Information System (GIS) as a digital communication tool for visualizing and communicating the spatial distribution of tourism potential in Kebumen RegencyThis research employs a descriptive-qualitative approach. The primary method utilized is the case study of Kebumen Regency’s tourism sector, focusing on collecting and digitizing spatial data. The data sources include field observations (to verify site coordinates and attributes), secondary data from the local Tourism Office (Dinas Pariwisata), and satellite imagery. The technical analysis employed is geospatial data processing using ArcGIS software to create, overlay, and analyze spatial layers (points, lines, polygons) representing various tourism categories (nature, cultural, culinary). The final output of the GIS processing is the development of an interactive WebGIS platform to serve as the digital communication interface. The WebGIS platform is tested for its user-friendliness and information clarity .The study successfully demonstrated that implementing a WebGIS platform significantly enhances the digital communication of tourism distribution in Kebumen. The interactive maps provided clear, multi-layered information (e.g., proximity to access roads, type of attraction, and visitor facilities) that was previously unavailable in a unified format.